Perceiving Others' Feelings: The Importance of Personality and Social Structure. (July 2015) - Sherman, Gary D.; Lerner, Jennifer S.; Renshon, Jonathan; Ma-Kellams, Christine; Joel, Samantha
Recent research has explored the relationship between social hierarchy and empathic accuracy—the ability to accurately infer other people's mental states. In the current research, we tested the hypothesis that, regardless of one's personal level of status and power, simply believing that social inequality is natural and morally acceptable (e.g., endorsing social dominance orientation, or SDO) would be negatively associated with empathic accuracy. In a sample of managers, a group for whom empathic accuracy is a valuable skill, empathic accuracy was lower for managers who possessed structural power and also for managers who endorsed social dominance, regardless of their structural power. Moreover, men were less empathically accurate than women, a relationship that may be explained by men's higher SDO and greater structural power. These findings suggest that for empathic abilities, it matters just as much what you think about social hierarchies as it does where you stand within them.